Short communication: Amphidromous goby postlarvae (penja) migration seasons and fisheries in West Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nurjirana, Burhanuddin AI, Keith P, Haris A, Afrisal M. 2021. Short communication: Amphidromous goby postlarvae (penja) migration seasons and fisheries in West Sulawesi, Indonesia. Biodiversitas 23: 375-380. Several gobioid species have amphidromous migration patterns; adult gobies spawn in their freshwater habitat, embryos are carried by river currents to reach the sea where they undergo a planktonic phase lasting several months before migrating to estuarine and then freshwater (predominantly riverine) environments to grow and breed. Around the island of Sulawesi in Indonesia, these migrating postlarvae have various local names; in West Sulawesi they are collectively known as penja, a popular fisheries commodity, but data on their migration patterns are limited. This study aimed to determine penja migration seasons and document some aspects of the penja fisheries in West Sulawesi. The research was conducted in the lower reaches of five rivers: the Mapilli, Mandar, Teppo, Palipi, and Lariang rivers. Penja samples were collected from fishermen's catches using several types of fishing gear such as seser (scoop nets), dariq or bunde (push nets), panesser (casting net) and other traditional or artisanal fishing equipment. Samples were also collected from traditional markets. The postlarvae were measured and grouped based on morphological characters. The results showed temporal differences in migration patterns between the five study sites, while external morphology indicated the presence of several species in migrating penja schools. During the rainy season, populations with a more diverse morphology were found than during the dry season.
Keywords: Amphidromy, larval fisheries, metamorphosis, migration patterns